2011
DOI: 10.4155/bio.11.81
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of DBS Within Drug Discovery: A Simple 2D-LC–MS/MS System to Minimize Blood- and Paper-Based Matrix Effects from FTA Elute™ DBS

Abstract: A generic 2D-LC-MS/MS system has been developed that eliminates paper-based matrix effects and eliminates or controls dried blood spot matrix effects for a panel of compounds extracted from FTA Elute™ with methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…LogD calc values suggested that the drug is positively charged at pH ≤ 3 (the amine group is protonated). When separated with RP–LC–MS and a mobile phase at pH = 3, DBS extracts from FTA Elute cards produced a more focused peak with an increased retention time than a hydro‐organic standard (no paper additive in the sample); that elution profile is consistent with the latter ion pairing mechanism (Clark & Haynes, ).…”
Section: Sample Handling and Preparationmentioning
confidence: 92%
See 1 more Smart Citation
“…LogD calc values suggested that the drug is positively charged at pH ≤ 3 (the amine group is protonated). When separated with RP–LC–MS and a mobile phase at pH = 3, DBS extracts from FTA Elute cards produced a more focused peak with an increased retention time than a hydro‐organic standard (no paper additive in the sample); that elution profile is consistent with the latter ion pairing mechanism (Clark & Haynes, ).…”
Section: Sample Handling and Preparationmentioning
confidence: 92%
“…Investigation of matrix effects for a panel of ten drugs (from FTA Elute cards, with MeOH for SLE) showed that they largely depended on the compounds, and both ionization suppression and enhancement were observed (Clark & Haynes, ).…”
Section: Sample Handling and Preparationmentioning
confidence: 99%
“…During the SPE optimization, DBS samples were prepared using chloroquine, desipramine and midazolam (50 ng/ml each) in rat blood. DMPK-C cards were selected for the DBS experiments as they are chemically untreated since cards impregnated with chemicals have been previously reported to interfere with the analyte signals [46].…”
Section: On-line Dbs-spe Methods Developmentmentioning
confidence: 99%
“…Paper‐based analytical devices (PADs) have shown great promise as point‐of‐care testing (POCT) platforms due to their advantages of being user‐friendly, rapid, robust, affordable, and scalable for manufacturing. Achieving efficient POCT within PADs has therefore found widespread applications, especially at home and in the field, such as clinical prognostics and diagnostics (Hu et al, ; Y. Wang, Li, Kong, & Sun, ), drug discovery (Clark & Haynes, ), genetic and forensic study (Hart et al, ), environmental monitoring (Peng, Zhang, Soeller, & Travas‐Sejdic, ), food safety analysis (Dzantiev, Byzova, Urusov, & Zherdev, ). For paper‐based POCT, cost‐effective, facile and sensitive detection rely heavily on the design and construction of probes.…”
Section: Introductionmentioning
confidence: 99%